'The verses of madness': schizophrenia and poetry. (20th December 2012) - Hankir, Ahmed Khaldoon; Holloway, David; Agius, Mark; Zaman, Rashid
Abstract : In the early 19th century, Lombroso introduced the concept of hereditary taint to describe the coexistence of 'madness' and creativity. In a recent investigation, Rust et al reported a study designed to test the traditionally assumed relationship between creativity and schizophrenia. They uncovered an association between creative originality and the positive cognitive aspects of schizotypal thinking. Poetry is not only the 'product' of psychopathology but it can also be utilised as a form of therapy: "My name is David Holloway, I am a 33 year old poet/blogger with paranoid schizophrenia. A poet called Charles Bukowski has described poetry as the 'ultimate psychiatrist', and I am a firm believer in this. The strongest part of my personality is my belief in the power of love. My recovery has relied heavily on medication, diet and exercise. However it is the power of poetry that has been my true inspiration."